Consumers Buying Behaviour and Challenges Faced by Consumers During COVID-19 Pandemic Regarding FMCG Products ( During Indian Lockdown) - et. al., Dr. Priyanka Rai, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Pandemics are the imminent health challenges for consumers whereby fear and panic are integral human responses historically. Panic behavior during pandemic is an expected response consumer threatens the ability to cope and destroy the existing balance in life. Consumers develop much-unexplained behavior which differs from region to region, culture to culture. Panic buying / increased buying behavior has been observed during public health emergencies since the ancient period. However, the exact psychological explanation responsible for it has not sought systematically. Therefore, the study is to intend a thrust to identify the possible psychological explanations behind the consumer buying behavior during pandemics. A perception of scarcity is strongly linked with the consumer buying behavior during pandemics, and collecting & saving behaviors increases if the scarcity develops for the immediate necessaries. It also creates a feeling of insecurity which in turn activates another mechanism to collect things. Panic buying also has been linked with perceived feeling of insecurity and instability of certain situations. Furthermore, supply disruption, a condition where normal product supply in supply chain interrupted, has been frequently observed during a disaster or other unwanted calamities. This also led to a feeling of insecurity. The objective of study is to analyze how pandemic affect consumer buying pattern and sentiments.